2007
DOI: 10.1080/01421590701317843
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for developing training programs for international medical graduates

Abstract: A 'hub and spoke' model is a useful model to adopt: a central coordinating office designs and implements programs informed by best available evidence, and clinical educators on site at healthcare facilities implement programs and provide direct assistance and orientation. Broad-based programs attending to orientation, doctor's families' needs, communication skills and clinical skills training are required. Support from health administrators is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
8
0
3
Order By: Relevance
“…Designing interventions for IMGs is a complex task; therefore, this synthesis describes the theory and processes needed to support IMGs to make a successful transition to their host country. The findings illustrate why interventions work (or not) and in what ways, thereby enabling those implementing interventions to make more informed choices.…”
Section: Discussionmentioning
confidence: 99%
“…Designing interventions for IMGs is a complex task; therefore, this synthesis describes the theory and processes needed to support IMGs to make a successful transition to their host country. The findings illustrate why interventions work (or not) and in what ways, thereby enabling those implementing interventions to make more informed choices.…”
Section: Discussionmentioning
confidence: 99%
“…It transpired in the interviews that the interviewed doctors would be supported significantly if a personal counselling service could be installed. Telephone hotlines or online counselling could be an approach to address this need, or even special training programs [32]. In Canada, for example, case management and mentorships were implemented with the aim to helping immigrant health workers navigate the licensure and examination processes [28,33].…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…37 Several studies have indicated that a structured induction process is a useful way to help integrate doctors during the transition to the NHS. 24,38- 43 Couser 43 suggests induction programmes need to be interactive, with small group work and role play relating activities to the workplace, but it is important to be mindful of trainees' different learning styles which may be related to cultural preferences. While the provision of induction will necessarily be the responsibility of employers, the content of such induction can be specified by government or regulator policy.…”
Section: At the Point Of Transitionmentioning
confidence: 99%
“…46 Educators and supervisors should also be aware of the different experiences and expectations of doctors from overseas, who may be less used to working in groups and more used to being a passive learner. 43 Cultural awareness training programmes may develop these skills in all elements of the workforce. Such programmes and mentoring interventions will also be necessarily the responsibility of the employer, but as with other initiatives these should be guided and standardised by government and regulator.…”
Section: On-going Workplace Supportmentioning
confidence: 99%